Adam Kazimierz Czartoryski’s comments on the art of translation as a manifestation of 18th century elites’ linguistic awareness - Hawrysz, Magdalena (Philology as the Ordering of Chaos: Language and Text Studies. Ad honorem Professoris Marci Cybulski, 2018)
The aim of the article is a description of translation theory, which can be reconstructed on the basis of the comments scattered in the work by Adam Kazimierz Czartoryski Thought about Polish writings [Myśli o pismach polskich]. This theory is considered to be an element of the 18th century linguistic awareness of then social elites. This subject can be observed through the prism of the following issues: 1) types of translation, 2) properties of Polish, 2) relation to neologisms, including borrowings. Adam Czartoryski’s reconstructed translatological concept is mature, multi-faceted and modern not only at this time, which is determined by the fact that not only aspects of the language system are included in the translation process but also cultural and communication perspectives are taken into account. The reconstructed theory complements the linguistic landscape of the Enlightenment elite; it also provides another proof of its high level.